Analysis of the quality health services on patient satisfaction at the Vina Estetica General Hospital Medan City - Tarigan, Gracia Hosanna Evelyn; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Science Midwifery, 2025)
Quality of health care refers to service excellence in meeting patient expectations and providing satisfaction. Quality service is essential because it is every customer's right and allows healthcare providers to compete. The quality of service and the value provided directly impact customer satisfaction. The quality of service they receive influences customer satisfaction, which affects the hospital's reputation and competitiveness. This study aims to analyze the quality of health services and their effect on patient satisfaction at RSU Vina Estetica. This study was conducted at RSU Vina Estetica, Medan City. The study population was all patients at RSU Vina Estetica, Medan City. The sampling technique was accidental sampling with a sample size of 306 respondents. The research method used was quantitative. This study is based on primary data obtained through questionnaires. The data analysis techniques used in this study are univariate, bivariate, and multivariate analysis using SPSS. Based on the study's results, it is known that reliability, responsiveness, and empathy influence patient satisfaction. The variables of physical evidence and assurance do not affect patient satisfaction. The most dominant factor influencing patient satisfaction is the variable of reliability.